P52-S State-dependent changes in cortical reactivity: comparison between direct cortical and peripheral stimulation. Issue 7 (July 2019) - Sarasso, Simone; Casarotto, Silvia; Fecchio, Matteo; Derchi, Camilla; Mazza, Alice; D'Ambrosio, Sasha; Viganò, Alessandro; Casali, Adenauer Girardi; Comolatti, Renzo; Comanducci, Angela; Rosanova, Mario; Massimini, Marcello; et al.
Abstract : Introduction: Peripheral as well as direct cortical stimulations have been classically used to probe the reactivity of thalamocortical circuits across brain states, showing consistent state-dependent modifications. Methods: Here we aim at directly comparing state-dependent changes across the wake/sleep cycle of the electroencephalographic (EEG) responses to transcranial magnetic stimulation (TMS – applied over premotor and parietal areas) and to electrical median nerve stimulation (EMNS - applied at an intensity able to reproducibly elicit thumb movements) in two groups of 8 healthy individuals each. Results: By tuning stimulation parameters, we roughly equalized the strength of brain activation elicited by TMS and EMNS during wakefulness and achieved a similar ( p = 0.8) overall (0–600 ms) global mean field power (GMFP). The time-course of wakefulness GMFP significantly peaked ( p < 0.05) at 0–50 ms for TMS and at 250–300 ms for EMNS. Compared to wakefulness, during NREM sleep: (1) the early (0–80 ms) as well as the late (80–600 ms) evoked EEG response significantly increased for TMS and decreased for EMNS ( p < 0.05); (2) these changes were associated to specific voltage topographies for TMS and EMNS; and (3) the overall spatiotemporal complexity decreased for both stimulation approaches. Conclusions: Despite a common reduction of complexity during sleep, brain activation elicited by the two stimulation approaches reveals different state-dependent changes, highlighting the presence of cortical bistability in the case of TMS and of subcortical gating in the case of EMNS.